STUDI TENTANG PENGARUH INTENSITAS HUJAN DAN KERAPATAN VEGETASI TERHADAP SEDIMENTASI DANAU BUATAN DAN JARINGAN SUNGAINYA DI KEBUN RAYA UNMUL SAMARINDA - Muhammad Syafrudin (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2011)
STUDI TENTANG PENGARUH INTENSITAS HUJAN DAN KERAPATAN VEGETASI TERHADAP SEDIMENTASI DANAU BUATAN DAN JARINGAN SUNGAINYA DI KEBUN RAYA UNMUL SAMARINDA The effects of rainfall intensity and vegetation density on sedimentation of artificial lake and it’s up-stream channel in Kebun Raya  Unmul SamarindaMuhammad SyafrudinLaboratorium Klimatologi Hutan, Jurusan Manajemen Hutan,Fakultas Kehutanan Universitas MulawarmanSamarinda ABSTRACTThis research was conducted in Kebun Raya Unmul Samarinda, an educational forest of Mulawarman University, It aimed to figure out the effect of rainfall intensity and vegetation, as well as estimated the amount of accumulated sediment in the lake and its up-stream channel. Statistically, this study revealed that two parameters (rainfall and vegetation) has contribute to the discharge flow and discharge suspended load sediment  and respectively it represented by its correlation coefficient which are 0.89-0.97 and 0.86-0.94. The values tend to closed to 1 and it indicate a positive correlation between parameters and discharge flow, as well as discharge suspended load sediment. Discharge flow and discharge suspended load sediment also related each other. The increases of discharge flow will lead to the increases of discharge suspended load sediment. Discharge suspended load sediment will increase whenever a lot of sediment from erosion flow to the river body. Discharge suspended load sediment increase in the river number 2, 4 and 5 because landuse changing occurred in the upper of the rivers outside of the forest. Potential sediment volume in a year at the each sampling points are 895.38 ton at River 1,464.23 ton at river 2,889.04 ton at river 3,336.76 ton at river 4,173.68 ton at river 5 and 335.56 ton at the lake.Key words : rainfall intensity, discharge flow, suspended load sediment.